Intelligent Capital, Organizational Learning, and Corporate Performance Influence Relationship. (22nd February 2022) - Lin, Li-Wei; Gan, Su-Mei; Wei, Shih-Yung
Abstract : Purpose . The purpose of this paper is to examine the factors influencing intelligent capital on enterprise performance. Design/Methodology/Approach . Based on dynamic panel data of listed companies in the Taiwan electronics industry from 2006 to 2017, we used the GMM estimation method. Findings . The findings of this study indicate that human capital, innovation capital, process capital, and customer capital all significantly improve enterprise performance through the mechanism of organizational learning. Research Limitations/Implications . Future research on cross-country studies of various forms of electronics industry would be worth conducting to determine regional differences in the development of electronics industry activities. Originality/Value . The empirical results demonstrate that human capital, process capital, and customer capital exert a significant promoting effect on enterprise performance, while innovation capital significantly inhibits improvement of enterprise performance.